Profile and determinants of delayed care-seeking and diagnosis among patients with imported malaria: a retrospective study in China, 2014-2021 - Tao Zhang; Duoquan Wang; Yingjun Qian; Wei Ruan; Ying Liu; Jing Xia; Hui Yan; Yuan Sui; Shenning Lu; Xian Xu; Jingjing Jiang; Xiaofeng Lyu; et al. (BMC, 2022)
Abstract Background In areas where malaria has been eliminated, delayed care-seeking and diagnosis of imported malaria are constant threats. This study aimed to describe the profile and determinants of delayed care-seeking and diagnosis among patients with imported malaria in China. Methods This retrospective study assessed surveillance data obtained from 2014 to 2021 in the Chinese provincial-level administrative divisions (PLADs) of Anhui, Henan, Hubei, and Zhejiang, and Guangxi. Epidemiological characteristics were analyzed using descriptive statistics. Furthermore, factors associated with delayed care-seeking and diagnosis among imported malaria cases were identified using multivariate logistic regression. Results Overall, 11.81% and 30.08% of imported malaria cases had delays in seeking care and diagnosis, respectively. During the study period, there was a decreasing trend in the proportion of imported malaria cases with delayed care-seeking (χ 2 = 36.099, P < 0.001) and diagnosis (χ 2 = 11.395, P = 0.001). In multivariate analysis, independent risk factors associated with delayed care-seeking include PLADs (Guangxi as reference), consultations in high-level facilities for the first medical visit, infections with non-Plasmodium falciparum species, and older age. However, PLADs (Guangxi as reference), the purpose of traveling (labour as reference), and infections with non-P. falciparum species increased the risk of delayed diagnosis. Delayed care-seeking (adjusted odds ratio: 1.79, P = 0.001) and diagnosis (adjusted odds ratio: 1.62, P = 0.004) were risk factors for severe disease development. Conclusions Based on this study's findings, we strongly advocate for improved access to quality healthcare to reduce the rate of misdiagnosis at the first visit. Infections caused by non-P. falciparum species should be highlighted, and more sensitive and specific point-of-care detection methods for non-P. falciparum species should be developed and implemented. In addition, education programs should be enhanced to reach target populations at risk of malaria infection. All these factors may reduce delayed care-seeking and diagnosis of imported malaria. Graphical Abstract